ШИМОЛИЙ–ҒАРБИЙ ЎЗБЕКИСТОН АРХЕОЛОГИК ОБЪЕКТЛАРИ: ТАДҚИҚОТЛАР ВА НАТИЖАЛАР - Каландаров, У. (SCIENCE and SOCIETY, 2016)
The article deals with the issues of learning and the results of archeological excavations of objects of antiquity and the Middle Ages in the Aral seaside delta of the Amudarya. On the territory of Karakalpakstan and Khorezm there were found new archeological discoveries (such as ancient inscriptions, coins, statuette, paintings) which are unique and cultural heritage of our ancestors.
Keywords: the south coast of the Aral sea; Guldursin kala; Al-Fir (Pil) kala; Ayaz kala; Tuprakkala; Kirkkiz kala; Kuykirilgan kala; Bazar kala; Janbas kala; Kizil kala; Anka kala; Doyaxotun; Jigarband; Kukhnauaz; Kuzalikir; Kaparas; Elkharas; Kurgan kala; Buldimsoz; Chirik Rabat; Babish Mulla; Jeti asar; Akchakhan kala